Religion, State Power, and Human Rights in China - Ownby, David (Religion and the Global Politics of Human Rights, 2011)
This chapter argues that human rights discourse remains marginal to the politics of religion in China, despite the efforts of the United States and international organizations to bring it in. There has been a liberalization of religious practice in China since the Cultural Revolution (1966–76) and the country's economic opening since 1979. By all accounts, the number of religious adherents in the country is surging, particularly within different forms of Protestant Christianity. While tolerating this development, the government has sought to carefully manage it. China recognizes freedom of belief as a human right, as well as religious practice—as long as the latter unfolds within a government-approved framework. Religious communities must be organized on a national basis, reflecting ongoing suspicion of external religious actors, a legacy of the involvement of missionaries in the colonial enterprise. And they must register with the Religious Affairs Bureau, which oversees the construction of new religious buildings, the printing of religious literature, and systems of seminaries and monasteries. Within this structure, local struggles for greater religious freedom have not focused on international human rights.